EXPLORING THE ROLE OF ONLINE PLATFORMS IN ENHANCING ESL LEARNERS' LANGUAGE SKILLS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The integration of online platforms into language learning has transformed the educational landscape, particularly for English as a Second Language (ESL) learners. This study explores the role of online language learning platforms in enhancing ESLlearners' language skills, with a focus on vocabulary, listening, speaking, and writing proficiency. The research aims to evaluate the effectiveness of popular platforms such as Duolingo, Babbel, and Memrise. Data was collected through pre- and post-tests,surveys, and interviews with 150 ESL learners who have engaged with these platforms for at least six months